Phytochemical analysis and DPPH scavenging activity of Combretum punctatum var. squamosum (Combretaceae), an ethnomedicinal plant of Mizoram. - Kawl Thanzami,; Bibhuti Bhusan Kakoti,; Christopher VL Famkima,; H Lalhlenmawia, (International Journal of Phytomedicine, 2016)
The main objective of the study is to determine the phytochemical constituents and the DPPH scavenging activity of the aqueous extract of Combretum punctatum var. squamosum. The phytochemical screening revealed that the crude aqueous extract contained phenols, flavonoids, phytosterols and diterpenes while alkaloids, glycosides, tannins, carbohydrates, proteins and amino acids were found to be absent. The total phenol and flavonoid content in the crude aqueous extract was found to be comparatively high, i.e. 111 mg/g GAE and 120.99 mg/g QE respectively. It was also found that the % DPPH scavenging activity was very high and comparable to the standard used. The IC50 value of the aqueous extract was found to be 1.76 mg/ml which is lower but comparable to the IC50 value of the standard.